Targeted alpha therapy with 212Pb or 225Ac: Change in RBE from daughter migration - Ackerman, N; De La Fuente Rosales, L; Falzone, N; Vallis, K; Bernal, M (Elsevier, 2018)
Targeted α-therapy (TAT) could be delivered early to patients who are at a high-risk for developing brain metastases, targeting the areas of the vasculature where tumor cells are penetrating into the brain. We have utilized a Monte Carlo model representing brain vasculature to calculate physical dose and DNA damage from the α-emitters 225Ac and 212Pb. The micron-scale dose distributions from all radioactive decay products were modeled in Geant4, including the eV-scale interactions using the Geant4-DNA models. These interactions were then superimposed on an atomic-scale DNA model to estimate strand break yields. In addition to 225Ac having a higher dose per decay than 212Pb, it also has a double strand break yield per decay that is 4.7 ± 0.5 times that of 212Pb. However, the efficacy of both nuclides depends on retaining the daughter nuclei at the target location in the brain vasculature. The relative biological effectiveness (RBE) of 225Ac and 212Pb are similar when the entire decay chains are included, with maxima of 2.7 ± 0.6 and 2.5 ± 0.5 (respectively), and RBE values of about 2 to a depth of 80 μm. If the initial daughter is lost, the RBE of 212Pb is completely reduced to 1 or lower and the RBE of 225Ac is approximately 2 only for the first 40 μm.